2020
DOI: 10.1177/1066896920951844
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Esophageal Ectopic Sebaceous Glands: Chronological Changes and Immunohistochemical Analysis

Abstract: Esophageal ectopic sebaceous glands are very rare lesions. A series of 5 cases in a single report has been the maximum number described in the English literature to date. We conducted a clinicopathologic study of 8 cases of esophageal ectopic sebaceous glands. The median patient age at the time of diagnosis was 60 years (range, 50-71 years), and 7 of the 8 patients were male. A focal lesion was observed in 7 cases, whereas 1 case exhibited multiple lesions throughout the esophagus. Four patients had previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They range from single lesions to over a hundred, from raised spots to plaques, and are predominantly found in the upper esophagus although they can occur anywhere in the esophagus [4]. Some cases may even have no distinguishable clinical lesions on EGD and may be found incidentally on biopsy [5]. A few studies have done follow-up endoscopies, and none have reported a malignant transformation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…They range from single lesions to over a hundred, from raised spots to plaques, and are predominantly found in the upper esophagus although they can occur anywhere in the esophagus [4]. Some cases may even have no distinguishable clinical lesions on EGD and may be found incidentally on biopsy [5]. A few studies have done follow-up endoscopies, and none have reported a malignant transformation [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…One suggests that ectopic sebaceous glands arise from metaplasia of esophageal mucous glands (a gland with the phenotype of salivary gland), while the other hypothesis suggests a congenital misplacement of the esophagus when the organ was developing from the endoderm. The increasing evidences suggesting that they originate as a result of an acquired metaplastic process [20][21][22]. There was one case of ectopic esophagus sebaceous glands in the setting of esophageal cancer [23], however, the ectopic esophageal sebaceous glands are known to have no malignant potential in previous literature [18].…”
Section: Discussionmentioning
confidence: 99%